The Function of SUMOylation and Its Role in the Development of Cancer Cells under Stress Conditions: A Systematic Review - Qi Zhao; Ying Ma; Zugui Li; Kexin Zhang; Minying Zheng; Shiwu Zhang (Stem Cells International)
Malignant tumors still pose serious threats to human health due to their high morbidity and mortality. Recurrence and metastasis are the most important factors affecting patient prognosis. Chemotherapeutic drugs and radiation used to treat these tumors mainly interfere with tumor metabolism, destroy DNA integrity, and inhibit protein synthesis. The upregulation of small ubiquitin-like modifier (SUMO) is a prevalent posttranslational modification (PTM) in various cancers and plays a critical role in tumor development. The dysregulation of SUMOylation can protect cancer cells from stresses exerted by external or internal stimuli. SUMOylation is a dynamic process finely regulated by SUMOylation enzymes and proteases to maintain a balance between SUMOylation and deSUMOylation. An increasing number of studies have reported that SUMOylation imbalance may contribute to cancer development, including metastasis, angiogenesis, invasion, and proliferation. High level of SUMOylation is required for cancer cells to survive internal or external stresses. Downregulation of SUMOylation may inhibit the development of cancer, making it an important potential clinical therapeutic target. Some studies have already begun to treat tumors by inhibiting the expression of SUMOylation family members, including SUMO E1 or E2. The tumor cells become more aggressive under internal and external stresses. The prevention of tumor development, metastasis, recurrence, and radiochemotherapy resistance by attenuating SUMOylation requires further exploration. This review focused on SUMOylation in tumor cells to discuss its effects on tumor suppressor proteins and oncoproteins as well as classical tumor pathways to identify new insights for cancer clinical therapy.